Aboriginal Peoples Survey, 2012 [Canada] ... : APS 2012 ... - Social And Aboriginal Statistics Division (Borealis, 2023)
The 2012 Aboriginal Peoples Survey (APS) is a national survey of First Nations people living off reserve, Métis and Inuit aged six years and over. The 2012 APS represents the fourth cycle of the survey and focuses on the topics of education, employment and health. It also collects information on language, income, housing and mobility. The 2012 APS collects unique and detailed data on education, employment and health, data which are not available from any other source. For example, although the 2011 National Household Survey collected data on level of education and on major field of study, the 2012 APS addresses additional topics such as number of schools attended, exposure to Aboriginal languages, school climate and support, frequency of reading, participation in extra-curricular activities, peer influences and plans for further schooling. The APS provides key statistics to inform policy and programming activities aimed at improving the well-being of Aboriginal Peoples. It is a valuable source of information ... : Migration from Nesstar, null ...